The Effect of Financial Risk, Product Risk, and Security Risk on Online Purchase Intention With Trust As A Medi-ating Variable For Make Over Cosmetic Products Purchased Online on Lazada - Nadya Afryani Dunggio; Rosyeni Rasyid (International Journal of Economics and Management Research, 2024)
This study aims to examine the influence of financial risk, product risk, and security risk on online purchase intention, with trust serving as a mediating variable, in the context of Make Over cosmetic products purchased through the Lazada e-commerce platform. Online shopping continues to grow rapidly in Indonesia, particularly in the beauty and cosmetic industry, which has become one of the most competitive sectors. However, despite its growth, consumers often face various risks when purchasing products online, such as concerns about financial security, product authenticity, and the protection of personal data. These perceived risks may hinder consumers’ willingness to make online purchases unless mitigated by trust in the platform and the brand. The research applies a quantitative method with a survey approach, utilizing a structured questionnaire distributed to 170 respondents who had purchased Make Over products via Lazada. Respondents were selected using purposive sampling to ensure relevance to the study’s objectives. Data analysis was carried out using Structural Equation Modeling (SEM) with SmartPLS software to test the hypothesized relationships between variables. The findings indicate that financial risk and product risk have a significant negative effect on consumer trust, while security risk does not show a significant influence. Furthermore, trust is demonstrated to have a strong and significant impact on online purchase intention. Trust also mediates the relationship between financial risk, product risk, and security risk with purchase intention, highlighting its crucial role as an intermediary factor. This research contributes to the literature on online consumer behavior by providing empirical evidence of the mediating role of trust in reducing perceived risk. Practically, the findings emphasize that cosmetic brands and e-commerce platforms need to enhance consumer trust by ensuring transparent product information, secure payment systems, and reliable service. Strengthening trust not only reduces risk perception but also encourages higher online purchase intention, which is essential for sustaining competitiveness in the digital marketplace.